Alterations in aerobic fitness and muscle deoxygenation during ramp incremental exercise in trained youth cyclists: a 3-year longitudinal study - Hovorka, M.; Simon, D.; Leo, P.; Prinz, B.; Nimmerichter, A. (Journal of Sports Sciences, 2023)
Alterations of aerobic fitness and muscle deoxygenation during a ramp incremental exercise test (GXT) were assessed on two occasions within a time-frame of 2.9 ± 0.1y in competitive youth cyclists. Nine cyclists (age, 14.5 ± 1.1y; peak oxygen uptake (VO2peak), 62.6 ± 4.2 mL.min-1.kg-1) participated in this investigation. VO2peak, the gas exchange threshold (GET) and the respiratory compensation point (RCP), as well as the muscle deoxygenation response pattern were determined during a GXT using open circuit spirometry and near-infrared spectroscopy, respectively. T-tests and Pearson`s correlations were used to assess effects of time on the dependent variables and relationships between changes of parameter estimates of aerobic fitness and the muscle deoxygenation response, respectively. Workrate and metabolic rate at GET (33 ± 20 and 42 ± 23%) and RCP (36 ± 20 and 40 ± 22%), and VO2peak (30 ± 18%) significantly increased throughout the study (P < 0.05). The muscle deoxygenation response showed a significant rightward shift from occasion one to two (P < 0.05). Alterations in the workrate/metabolic rate at RCP, and VO2peak, were correlated with alterations of the muscle deoxygenation response (R = 0.71-0.89, P < 0.05). Together, this is thought to indicate a superior muscle perfusion within the tissue of interrogation at the same metabolic rate on occasion two vs. one, which partially contributed to the improved aerobic fitness in the cyclists herein.